(3GdEOGQI GdeYGUQI (B:s (3GdeHGOF(B- (3GdhXGFa(B- (3GdeeGQSI (B/s - (3Ndjd, ehSis ((3HjQhJ(B: s (3GdeDSSI GdLGeYjI ddOQGSGJ hGdfTQ hGdJhRjY(B, s, 2005)
(3eaghe hCgejI GdEOGQI(B- (3GdeOjQjf(B- (3GdeMjWGJ hGdeJZjQGJ GdMOjKI(B- (3GdJNWjW GdEOGQj(B- (3GdJfXje GdEOGQj(B- (3GdJhLjg GdEOGQj(B- (3GdEJUGd GdEOGQj(B- (3GdJaGhV(B- (3GdJMajR GdEOGQj(B- (3GdQbGHI GdEOGQjI(B- (3GdJbjje GdEOGQj hGdJbhje(B- (3GdbQGQGJ GdEOGQjI(B- (3GdbjGOI GdEOGQjI(B.s
(3GdeQGLY U(B.226s
Keywords: (3EOGQI GdCYeGd(B- (3GdadSaIs; (3GdEOGQI GdYGeIs; (3GdEOGQI(B- (3GdadSaIs